(untitled) (Aintelia Science Notes, 2022)
Darts game is a popular game where people compete in competition while having fun. Although most people do not know, the dartboard design used while playing the game is an optimization problem studied by different researchers. A dartboard design that will increase the competition in the game and make the game more complex can be set up as a combinatorial optimization problem. This study used the Simulated Annealing algorithm to obtain an optimal dartboard design. Contrary to the algorithm’s classical structure, it aims to achieve better results by using more than one neighborhood structure. By running the designed algorithm with four different objective functions, the best designs were tried to be obtained. As a result, in addition to the existing designs in the literature, two new designs are proposed that provide good solutions for all objective functions.